2017
DOI: 10.1016/j.molmet.2017.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Maternal obesity programs increased leptin gene expression in rat male offspring via epigenetic modifications in a depot-specific manner

Abstract: ObjectiveAccording to the Developmental Origin of Health and Disease (DOHaD) concept, maternal obesity and accelerated growth in neonates predispose offspring to white adipose tissue (WAT) accumulation. In rodents, adipogenesis mainly develops during lactation. The mechanisms underlying the phenomenon known as developmental programming remain elusive. We previously reported that adult rat offspring from high-fat diet-fed dams (called HF) exhibited hypertrophic adipocyte, hyperleptinemia and increased leptin mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 55 publications
(113 reference statements)
4
28
0
Order By: Relevance
“…At PND21, HF male offspring displayed higher iWAT and pWAT deposit weights with increased leptin mRNA levels, marked adipocyte hypertrophy, and hyperplasia. HF 9M male rats showed persistent increased pWAT mass with elevated leptin mRNA levels, whereas this expandable phenotype was no longer observed in iWAT (2, 23). By contrast, both fat pads had persistently lower PPARγ expression.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…At PND21, HF male offspring displayed higher iWAT and pWAT deposit weights with increased leptin mRNA levels, marked adipocyte hypertrophy, and hyperplasia. HF 9M male rats showed persistent increased pWAT mass with elevated leptin mRNA levels, whereas this expandable phenotype was no longer observed in iWAT (2, 23). By contrast, both fat pads had persistently lower PPARγ expression.…”
Section: Discussionmentioning
confidence: 90%
“…Given that metabolic signals, including hormonal signaling pathways, play critical roles in determining chromatin structure (28), this study assessed the plasma metabolic profile in HF offspring. We previously reported that weaned and adult HF offspring exhibited hyperleptinemia (2, 23). The present study showed that serum triacylglycerol and insulin levels were elevated in HF male offspring at PND21 (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations